The integration of supply chain value stream mapping and discrete event simulation for lead time reduction of warehouse operations in a pharmaceutical organization - Muzamil Ahmed, Zainul Abideen (2020)
The supply chain lead time build-up that occurs due to inventory handling inside the warehouse that comprises of a set of waiting time, queuing time, and unwanted delays creates difficulties in meeting demand shocks and third party stakeholder requirements. These problems consistently prevail and tend to evolve no matter how sophisticated production planning is done. In that case, a pharmaceutical warehouse supply chain inventory would be a real challenge to study or map to find out ways for further improvements. In this research, a Malaysian pharmaceutical company’s warehouse was considered for the study. After a detailed field work and literature gap inferences, a case study approach was considered to be the best methodology for this study. It was applied to find effective ways to introduce lean integrated simulation modelling using Supply Chain Value Stream Mapping (SCVSM) and Discrete Event Simulation (DES) to capture, record, analyze, and reduce inventory waiting time, delays, queues and other wastes for a selected particular product family. After several lean suggestions in the future state SCVSM, the results of this study show that there is a considerable improvement in the warehouse lead time. The production lead time and total process time has decreased by 51.43% and 44.41 % respectively. The total value-added time has increased by 29.21 % the non-value added time has decreased by 31.86 %. In the second segment, there was a 20.22 % increase in the value-added time and a 23.17 % decrease in the non-value added time. DES models were then developed to replicate the entire operations for the purpose of present and future state simulation along with the suggestions for improvements. This study proved to possess strong managerial and practical implications that shall help in better decision making by deeply understanding the supply chain activities that occur as discrete events inside a warehouse.